Intensity of directed personal training in dance modalities - Conesa Ros, E. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Currently, the general adult population uses a multitude of sporting modalities, directed activities and locomotion modalities to carry out the daily physical activity recommended by the organisms and institutions of reference. Among these new disciplines has been emerged strongly in recent years different modifications of dance activities and modern dances. To determine if these disciplines require the intensity of effort recommended by the international scientific literature, this work analyzed the relative intensity expressed as a percentage of maximum heart rate (%HRmax) and reserve (%HRR) in dance styles of Hip-Hop and Salsa with programmed and expert-led sessions. Seven young people with experience in the practice of activities directed by musical support performed 5 standardized and equal sessions in volume, intensity and steps for each of the two modalities under study. The results show that Hip-Hop dance has a medium and maximum intensity requirement that allows it to be classified as vigorous activity (%HRR 64% and 86%), whereas Salsa should be classified as moderate intensity (%HRR 57% and 77% %). Although both modalities meet the requirements of recommended intensity for the healthy adult population, the greater relative intensity of the Hip-Hop allows the total weekly volume to be reduced to about 75 minutes to reach the marked heart-healthygoals, whereas the Salsa requires at least 150 minutes per week.